An ulcerated lesion due to HSV-2 infection with a CD56+ cell predominant inflammatory infiltrate - Fernandez-Flores, Angel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
CD56+ rich inflammatory infiltrates have been described in several cutaneous inflammatory conditions. However, CD56+ cells rarely account for more than 10%of the cells in such infiltrates. In certain conditions, such as insect bites or infection with herpes virus, CD56+ cells can be up to 43% of the cells in the infiltrate. This contrasts with what is observed in natural killer (NK)-cell lymphomas, which show a diffuse, atypical infiltrate in whichmost of the cells are CD56+. In this report, we describe a lymphocytic infiltrate in an ulcerated lesion on the lip of a 53-year-old man resulting from infection with herpes simplex virus type 2. CD56+ cells represented 80 to90% of the infiltrate, showing atypical morphologic features, and clusters of CD56 positive cells were also observed.
Keywords: Biopsija; Biopsy; diagnostika; Herpes simpleks; Herpes Simplex; Immunohistochemistry; Imunohistokemija; Limfocitni podtipi; Lymphocyte Subsets; Middle Age; Oral Ulcer; Simpleksvirus; Simplexvirus; Srednja leta; Usta, ulcus